The (dis)obedient occupational therapist: A reflection on dissent against disciplinary propaganda/ O terapeuta ocupacional (des)obediente: uma reflexão dissidente contra a propaganda disciplinar - Turcotte, Pier-Luc; Holmes, Dave (Cadernos Brasileiros de Terapia Ocupacional, 2021)
Introduction: Despite struggling to establish itself as an autonomous profession, occupational therapy remains extensively regulated and controlled by discursive authorities inside and outside the discipline. After overcoming the profession’s reformist ideals, the military governance that supported its rapid expansion morphed into civil institutions but both were based on similar grounds: occupational therapists should obey a strict set of rules while disobedience and dissent are consistently repressed or silenced. Objective: The objective of this article is to deconstruct dominant (consensual) discourses that shape the status quo in occupational therapy and envision alternative paths for the development of the discipline. Method: Drawing on the work of Erich Fromm and Jacques Rancière, we propose a (critical) theoretical analysis of the concepts of disobedience and dissensus as they apply to occupational therapists. Results: The concepts of disobedience (Fromm) and dissensus (Rancière) can be used to revisit the consensus shaped by discursive authorities inside and outside occupational therapy and expose the political nature of such processes. We argue that remaining oppressive forces similar to those of a warfare regime persist in regulating occupational therapy practice and knowledge by enacting a form of ‘disciplinary propaganda.’ Rather than threatening the development of the discipline, disobedience and dissensus constitute critical responses to disrupt dominant discourses and give rise to healthier concepts. Conclusion: The use of politically charged terms such as disobedience or dissensus can be seen as controversial and unsettling for a profession like occupational therapy but we believe they are necessary for the future of our discipline.